Great Dream of KH Ahmad Dahlan in the Development of Islamic Education in Indonesia - Hilalludin Hilalludin (Journal of Noesantara Islamic Studies, 2024)
Education in Islam faced a division between religious and secular components by the late twentieth century, with Islamic institutions often excluding religious education while general education institutions integrated secular knowledge. This paper explores the reform efforts of KH. Ahmad Dahlan in addressing these educational challenges in Indonesia, emphasizing the integration of religious and general education. Using a literature review methodology, the research analyzes Dahlan's influence on the development of Islamic education through his establishment of the Muhammadiyah organization. His vision included providing inclusive, quality education, fostering Islamic character, and modernizing educational systems. The findings highlight Dahlan's impact on the Indonesian education landscape, particularly through the integration of religious and general knowledge, character building, and community empowerment. His legacy continues to inspire the advancement of Islamic education in Indonesia.